2015
DOI: 10.1080/02678292.2015.1033772
|View full text |Cite
|
Sign up to set email alerts
|

Role of the elastic constants of a liquid crystal with positive dielectric anisotropy in the electro-optic characteristics of fringe-field switching mode

Abstract: 2015): Role of the elastic constants of a liquid crystal with positive dielectric anisotropy in the electro-optic characteristics of fringe-field switching mode, Liquid Crystals, We investigated how the electro-optic characteristics of the fringe-field switching (FFS) liquid crystal (LC) mode are affected by elastic constants of LCs. Unlike conventional liquid crystal (LC) devices, in which mainly the dielectric torque determines reorientation of LC, the field-induced LC reorientation in the fringe-field switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For Keff in FFS and IPS, the twist elastic constant (K22) has been mainly used. It was found that there is a close relation of the twist elastic constant (K22) and the splay elastic constant (K11) and that K22 can be approximated as about half of K11 [4] [5]. A reasonable correlation of γ1/K11 and response time is given in case of FFStype LCDs On the panel structure side, to achieve very fast response times, a reduction in d is absolutely necessary.…”
Section: Rotational Viscosity Cell Gap Dielectric Anisotropy Operatin...mentioning
confidence: 97%
“…For Keff in FFS and IPS, the twist elastic constant (K22) has been mainly used. It was found that there is a close relation of the twist elastic constant (K22) and the splay elastic constant (K11) and that K22 can be approximated as about half of K11 [4] [5]. A reasonable correlation of γ1/K11 and response time is given in case of FFStype LCDs On the panel structure side, to achieve very fast response times, a reduction in d is absolutely necessary.…”
Section: Rotational Viscosity Cell Gap Dielectric Anisotropy Operatin...mentioning
confidence: 97%